Forensic and security applications of a long‐wavelength dispersive Raman system. (18th February 2015) - Ali, Esam M. A.; Edwards, Howell G. M.; Cox, Rick
Abstract : A novel dispersive system operating at 1064‐nm excitation and coupled with transfer electron InGaAs photocathode and electron bombardment CCD technology has been evaluated for the analysis of drugs of abuse and explosives. By employing near‐IR excitation at 1064‐nm excitation wavelength has resulted in a significant damping of the fluorescence emission compared to 785‐nm wavelength excitation. Spectra of street samples of drugs of abuse and plastic explosives, which usually fluoresce with 785‐nm excitation, are readily obtained in situ within seconds through plastic packaging and glass containers using highly innovative detector architecture based upon a transfer electron (TE) photocathode and electron bombarded gain (EB) technology that allowed the detection of NIR radiation at 1064 nm without fluorescence interference. This dispersive near‐IR Raman system has the potential to be an integral part in the armoury of the forensic analyst as a non‐destructive tool for the in‐situ analysis of drugs of abuse and explosives. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A novel dispersive system operating at 1064‐nm excitation has been evaluated for the analysis of drugs of abuse and explosives. Street samples of drugs of abuse and plastic explosives which usually fluoresce with visible or 785‐nm excitations were successfully analysed without interfering fluorescence backgrounds.